BETA DOSE EVALUATION ALGORITHM FOR CaSO4:Dy BASED TLD BADGE USED IN COUNTRYWIDE PERSONNEL MONITORING PROGRAMME IN INDIA. Issue 1 (7th October 2016) - Rakesh, R. B.; Kumar, Munish; Sneha, C.; Ratna, P.; Datta, D.
Abstract: The prevalent algorithm for the estimation of beta dose, which in turn is used for estimation of skin dose for exposures involving beta radiations was observed to significantly overestimate the dose in individual monitoring based on CaSO4 :Dy TLD badge in India. A new algorithm has been developed by estimating the correction factor from the response of dosemeter to different beta sources at various angles of incidence. The correction factor was observed to vary linearly with the ratio of the responses of dosemeter element without filter ( D 3 ) and dosemeter element under Perspex filter ( D 2 ). The correction factor determined using the ratio of D 3 and D 2 was applied to the response ( D 3 ) of dosemeter element without filter for estimation of beta dose. Protocol for identification of beta in the mixed gamma beta fields was defined such that it resulted in nearly same correction factor for given beta source in both gamma beta mixed fields and pure beta fields. The beta dose evaluation algorithm has provided the beta dose estimation within the required accuracy for >90% cases obtained from national quality assurance test data from different laboratories.